Application of Health Behavioral Models in Smoking Cessation - A Systematic Review - Karthikayan Ravi; K Indrapriyadharshini; P D Madankumar (Wolters Kluwer Medknow Publications, 2021)
Background: Smoking is a significant risk factor for morbidity and mortality. Health education by health promotion is such a gauge to control tobacco epidemic at both national and multinational levels. Objectives: The objectives of the study were to systematically review the literature to identify models for health behavior change and evaluate evidence for their effectiveness in smoking cessation. Methods: A systematic review of the literature identified four peer-reviewed studies describing two smoking cessation behavioral interventional models (transtheoretical model [TTM] and health belief model [HBM]) between 2008 and 2018. Electronic databases MEDLINE (PubMed) and Google Scholar and Trip database were carried out. There were two randomized controlled trials and two nonrandomized controlled interventional studies. There was a high degree of homogeneity of design, definition of smoking and smoking abstinence, and implementation, followed by comparison of studies. All included studies have evaluated outcome by stage of changes (component of TTM model) and therefore show the reduction of smoking rate. All studies did not have blinding of study participants, leading to a higher risk of bias in the outcome. Results: There was a statistically significant difference between TTM-based interventional group and control group in smoking cessation rate. While comparing HBM- and TTM-based behavioral counseling, there was no statistically significant difference in smoking cessation rate. Conclusion: Both HBM- and TTM-based trainings were found to have positive effects on both smoking cessation and progression between the stages.